Influences of Waiting Time on Driver Behaviors While Implementing In-Vehicle Traffic Light for Priority-Controlled Unsignalized Intersections - Bo Yang; Rencheng Zheng; Tsutomu Kaizuka; Kimihiko Nakano (Journal of Advanced Transportation)
In-vehicle traffic lights that assist drivers in crossing intersections are in development; however, the availability of the in-vehicle traffic light will be limited if the waiting time of a vehicle is not considered in actual traffic conditions, especially at priority-controlled unsignalized intersections that normally consist of one major and two minor roads. The present study therefore investigated the effects of the waiting time on driver behaviors to improve the in-vehicle traffic light for the priority-controlled unsignalized intersections. Gap acceptance theory that considers the waiting time was adopted in the implementation of the in-vehicle traffic light, to assist minor-road drivers in passing through the intersections by selecting appropriate major-road gaps. A driving simulator experiment involving 12 participants was performed for the minor and major roads, by applying the in-vehicle traffic light with and without the consideration of waiting time. Results demonstrate that the maximum acceleration strokes of minor-road vehicles were significantly reduced, indicating a lower possibility of aggressive driving when the in-vehicle traffic light was applied while considering the waiting time. Meanwhile, an improved steering stability was observed from the driver behaviors at the intersections, as the maximum lateral acceleration of minor-road vehicles significantly decreased when the waiting time was considered.